Are the police embracing evidence-informed practice? A view from England and Wales - Hunter, Gillian C. (Policing and society, 2019)
The What Works Centre for Crime Reduction (WWCCR) in the UK’s College of Policing has a key role in promoting the use of research in policing. Since 2014, the WWCCR has aimed to review - and make accessible - research to better inform and target crime reduction and to build police capacity to identify, evaluate and apply research evidence to practice. This comes amidst significant changes to entry requirements for policing in the UK as part of efforts to further professionalise the service and prepare for future challenges in policing. We report findings from in-depth interviews with senior police officers from forces across England and Wales, conducted as part of a three-year evaluation of the WWCCR. These interviews explored the traction of ‘evidence-based practice’ among senior officers and showed shifts over time in their accounts of the value placed on research and how it is promoted and used within their force. Additionally, an online survey across policing ranks, conducted in 2016, found differences by seniority in perceptions about the relevance of research for policing, and the level of organisational support for it. Findings are used to consider the status of research evidence in policing and its development within a policing profession.